328PA retrospective analysis of patients with non-small cell lung cancer who developed drug-induced lung disorder by immune checkpoint inhibitors. (24th November 2019) - Hayashi, F; Taniguchi, H; Takayuki, S; Umeyama, Y; Dotsu, Y; Gyotoku, H; Senju, H; Takemoto, S; Yamaguchi, H; Ono, S; Tomono, H; Shimada, M; et al.
Abstract: Background: The presence of the immune-related adverse events (irAEs) has been reported as a preferred marker of the efficacy of immune checkpoint inhibitors (ICIs) in non-small cell lung cancer (NSCLC) patients. However, there are only a few studies that focused on the relationship between the efficacy of ICIs and the severity or a high-resolution computed tomography (HRCT) scan pattern of drug-induced lung disorder (DILD). Methods: We conducted a retrospective study of patients with NSCLC who were treated with ICIs between January 2016 and June 2019 in our institution. We especially focused on the patients who developed DILD during ICIs treatment, and analyzed the clinical information and HRCT pattern of DILD to investigate the prognosis of patients who developed DILD. Assessment of treatment response was evaluated using the response evaluation criteria in solid tumors version 1.1. Severity of DILD was classified by grade according to pneumonitis in Common Terminology Criteria for Adverse Events (CTCAE) version 5.0. Results: Total 182 patients were enrolled, including 20 patients who received chemotherapy with ICIs. Among the 182 patients, 32 patients (17.6 %) developed DILD and CTCAE grade 1/2/3/4/5 were 10/7/9/2/4 patients, respectively. The median progression-free survival was 100 and 93 days, (P = 0.324, Log-rank Test) and overall survival was 415 and 501 days (P = 0.0951, Log-rank Test) in patients with or without DILD, respectively. The median period from the first ICI treatment to onset of DILD was significantly shorter in the Grade 3/4/5 group than Grade 1/2 group; 22 and 72.5 days, respectively (P = 0.029, Mann-Whitney U test). Analyzing HRCT findings according to ATS/ERS/JRS/ALAT GUIDLINE, patients who presented consolidation had better prognosis than those with comprehensive GGO. In 4 patients with Grade 5 pneumonitis developed with comprehensive GGO and the period from onset of DILD to death was extremely short; median 2 days. Conclusions: Our retrospective study suggested that development of DILD was not preferred in terms of prognosis in NSCLC patients. Physician should be alerted for the patients who developed early-onset, severe DILD with comprehensive GGO during ICI treatment. Legal entity responsible for the study: Hiroyuki Yamaguchi. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.